2011
DOI: 10.1111/j.1600-6143.2011.03701.x
|View full text |Cite
|
Sign up to set email alerts
|

Former Smoking Is a Risk Factor for Chronic Kidney Disease After Lung Transplantation

Abstract: Chronic kidney disease (CKD) is a common complication after lung transplantation (LTx).Smoking is a risk factor for many diseases, including CKD. Smoking cessation for >6 months is required for LTx enlistment. However, the impact of smoking history on CKD development after LTx remains unclear. We investigated the effect of former smoking on CKD and mortality after LTx. CKD was based on glomerular filtration rate (GFR) ( 125 I-iothalamate measurements). GFR was measured before and repeatedly after LTx. One hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
2
13
0
8
Order By: Relevance
“…[168][169][170][171][172][173][174][175][176] Cigarette smoking is also a major risk factor for the initial development or worsening of preexisting CKD in patients with human immunodeficiency virus infection, chronic obstructive pulmonary disease, diabetes, diabetic nephropathy, hypertension, autosomal polycystic kidney disease, primary glomerulopathies, lupus nephritis, and those who are obese or who have undergone a lung transplant. [177][178][179][180][181][182][183][184][185][186][187] In addition, smoking by either the donor or recipient has been shown to adversely influence the function and survival of transplanted kidneys and overall patient survival. 170,171,188,189 Allograft survival and function both worsen with increasing pack-years smoked.…”
Section: Hypertensionmentioning
confidence: 99%
“…[168][169][170][171][172][173][174][175][176] Cigarette smoking is also a major risk factor for the initial development or worsening of preexisting CKD in patients with human immunodeficiency virus infection, chronic obstructive pulmonary disease, diabetes, diabetic nephropathy, hypertension, autosomal polycystic kidney disease, primary glomerulopathies, lupus nephritis, and those who are obese or who have undergone a lung transplant. [177][178][179][180][181][182][183][184][185][186][187] In addition, smoking by either the donor or recipient has been shown to adversely influence the function and survival of transplanted kidneys and overall patient survival. 170,171,188,189 Allograft survival and function both worsen with increasing pack-years smoked.…”
Section: Hypertensionmentioning
confidence: 99%
“…In addition, 74% of the liver transplant patients and approximately 50% of the lung transplant patients in studies demonstrating an association between smoking and chronic kidney disease development were immunosuppressed with CsA [13,14]. Surprisingly, none of these studies referenced the potentially deleterious synergic association between cigarette-smoking-related renal injury and CsA-induced nephrotoxicity in this population.…”
Section: Discussionmentioning
confidence: 98%
“…Surprisingly, none of these studies referenced the potentially deleterious synergic association between cigarette-smoking-related renal injury and CsA-induced nephrotoxicity in this population. Few authors have included short secondary comments regarding the potential synergism between cigarette smoking and calcineurin inhibitors that could induce vascular injury in transplant patients [13,19,20]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that cigarette smoking significantly increased the risk of reduced eGFR in patients with type 2 diabetes [13]. And former smokers generally had a significantly lower eGFR than never smokers from 6 months after lung transplantation [14]. All these studies indicated that cigarette smoking is an independent risk factor for CKD.…”
Section: Introductionmentioning
confidence: 99%